2015
DOI: 10.1007/s10995-015-1704-3
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Inter-Parental Conflict Across 10 Years of Childhood: Data from the Longitudinal Study of Australian Children

Abstract: Rates of child exposure to inter-parental conflict are high and appear to be increasing, with at least one million Australian children affected annually. To-date, there is no established prevalence for inter-parental conflict that includes the more common but less severe forms for young families in the wider Australian community. The current study aims were to examine the prevalence, persistence, and the individual, family and socio-economic context of inter-parental conflict. Data were from four waves of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
42
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 23 publications
3
42
2
Order By: Relevance
“…These statistics likely represent a gross underestimation, given that family conflict statistics are obtained from the police, child welfare and family court data, which only captures the most severe forms of psychological, physical and emotional abuse. Researchers like Westrupp [3] have concluded that community prevalence of inter-parental conflict is likely much higher than these statistics indicate.…”
Section: Literature Meta-analysismentioning
confidence: 98%
See 4 more Smart Citations
“…These statistics likely represent a gross underestimation, given that family conflict statistics are obtained from the police, child welfare and family court data, which only captures the most severe forms of psychological, physical and emotional abuse. Researchers like Westrupp [3] have concluded that community prevalence of inter-parental conflict is likely much higher than these statistics indicate.…”
Section: Literature Meta-analysismentioning
confidence: 98%
“…For instance, in Australia, researchers have found that inter-parental conflict affects millions of children annually [3]. The number of reported family violence cases in Australia has increased in the last six years.…”
Section: Literature Meta-analysismentioning
confidence: 99%
See 3 more Smart Citations